Electromagnetic fields of cellular communication as risk factors able to produce negative effects on the central nervous system of children and adolescents (review). Part 1. Modeling. parameters of electroencephalography and sensorimotor reactions - N.I. Khorseva; N.I. Khorseva (Analiz Riska Zdorovʹû)
It is quite relevant to investigate possible outcomes of exposure to radio frequency electromagnetic fields (RF EMF) since contemporary children and adolescents have become active users of the most advanced technologies. They are especially susceptible to electromagnetic factors; therefore, it is necessary to have a proper insight into outcomes of such exposures for the body.